Matlab based SAR signal processor for educational use - Deo, R.; Jamod, A.; Gopu, V. D. R.; Rao, Y. S. (2012 IEEE International Geoscience and Remote Sensing Symposium, 2012)
This paper is an attempt to help the beginners and the students to learn the basics of the SAR signal processing in a simple and easy way using MATLAB. The signal processing of SAR data is very important for generating various data products for different applications and analysis of land features. The SAR raw data for signal processing is a two dimensional array which contain sampled echoes in the complex form. Pulse compression techniques are used to compress energy of echoes and thereby increasing the resolution of SAR. To obtain the final image the range compression, Doppler centroid frequency estimation, range cell migration correction, azimuth compression etc. are implemented in such a way that any user can understand very easily. Advantage of the developed code in MATLAB is that it does not need a vast programming knowledge to be able to customize it. The developed code will be available to all users for educational and training purposes.